Impact and significance of alkaline-oxidant pretreatment on the enzymatic digestibility of Sphenoclea zeylanica for bioethanol production - Phuong Thi Vu (2018)
© 2017 Elsevier Ltd Gooseweed (Sphenoclea zeylanica Gaertn.) is a pest on the rice field that has a potential to be a promising substrate for bioethanol production. Dry powdered gooseweed was firstly pretreated with 1% NaOH, following 1% H 2 O 2 at variety conditions. The hydrolysis process was set at 50 °C for 24–72 h with enzyme cellulase (β-glucosidase) while the fermentation process was carried using Saccharomyces cerevisiae TISTR 5020 at 33 °C for nine days. The ethanol concentration was recorded for three, five, seven, and nine days using an ebulliometer. The results showed that the treatment with only 1% NaOH for 24 h has the highest sugar performance. In regard with hydrolysis, the optimum retention time was at 24 h. Lastly, the highest ethanol concentration was achieved at 11.84 g/L after five days and a rapid decreasing after seven to nine days was also observed.